Positive electrode material of sodium ion secondary battery, preparation method of positive electrode material, sodium ion secondary battery and electric equipment
By introducing metal elements with a compound valence ≥2 into the sodium ion battery positive electrode material, the bonding strength between doped metal elements and oxygen is enhanced, and the problem of the structural stability of the sodium ion battery positive electrode material decreases at high voltage is solved, and the high capacity and cyclic stability are improved.
Patent Information
- Application Number
- CN202411769929.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The structural stability of existing sodium ion battery positive electrode materials decreases when the voltage is greater than 4.0V, resulting in a significant decrease in the retention rate of circulation capacity.
The positive electrode material of NaaNixFeyMnzM1-x-y-zO2 is prepared by introducing metal elements with a compound valence of ≥2, such as Al, Ti, Zr, etc., and is prepared by co-precipitation method and multi-stage calcination method to enhance the bonding strength of the doped metal elements and oxygen and reduce the content of high-active O-free oxygen.
The structural stability of the sodium-electric O3 structure is improved, the side reaction between O-free oxygen and the electrolyte is suppressed, the high capacity is ensured, and the circulation stability of the material is greatly improved.
Smart Images

Figure CN119581548A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion batteries, and in particular to a positive electrode material of a sodium ion secondary battery and a preparation method thereof, a sodium ion secondary battery and electrical equipment. Background Art
[0002] Currently, lower-cost sodium-ion batteries (SIBs) are needed to promote the large-scale application of electric vehicles and energy storage. Since the Na content in the alkali metal layer dominates the reversible capacity, O3-structured layered oxide cathode materials (NaTMO2) are highly anticipated due to their special advantages in energy density and production cost, especially when the voltage is increased to above 4.0V, they can release a specific capacity of ≥130mAh / g. However, when the voltage is greater than 4.0V, the valence state of the Ni element will increase to +4, and at this time, Ni 4+ The Fermi level of an element and the O in the lattice 2- There is overlap, resulting in O 2- Produced by charge transfer and oxidation to O - or O, will produce oxygen vacancies and structural rearrangements that deteriorate the structural stability of the positive electrode material, resulting in a significant decrease in the capacity retention rate during the cycle. However, the introduction of elements with a valence greater than +2 in the transition metal layer through directional doping technology can stabilize the lattice oxygen activity under high SOC, thereby achieving the effect of improving the stability of the main crystal layer.
[0003] Therefore, how to improve the bonding strength between doped metal elements and oxygen and reduce the highly active O - The free oxygen content makes the sodium-ion battery O3 structure have strong structural stability, thus inhibiting the formation of O - The side reaction between free oxygen and the electrolyte can significantly improve the cyclic stability of the material while ensuring the release of a higher gram capacity, and has become a hot topic of current research. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode material for a sodium ion secondary battery and a preparation method thereof, a sodium ion secondary battery and electrical equipment to solve the above problems.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] The present application provides a positive electrode material for a sodium ion secondary battery, wherein the chemical formula of the positive electrode material for the sodium ion battery is Na a Ni x Fe y Mn z M 1-x-y-zO2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1, and the M element is a metal element with a valence ≥2.
[0007] Optionally, the M element includes at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0008] The present application also provides a method for preparing a positive electrode material for a sodium ion secondary battery, comprising:
[0009] Mixing the solutions of the nickel source, the iron source, the manganese source and the first M element source to obtain a mixed solution, and obtaining a precursor material by a coprecipitation method;
[0010] The precursor material is mixed with a sodium source and then first calcined, and then cooled to obtain a primary material;
[0011] The primary material is mixed with a second M element source and then subjected to a second calcination to obtain the positive electrode material of the sodium ion battery.
[0012] Optionally, the nickel source includes nickel sulfate; the iron source includes iron sulfate; and the manganese source includes manganese sulfate.
[0013] Optionally, the first M element source includes a sulfate of at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0014] Optionally, the metal element in the second M element source includes at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0015] Optionally, after the precursor material is prepared, the process further includes solid-liquid separation, washing, and drying, wherein the drying temperature is 100-300° C. and the drying time is 2-6 hours.
[0016] Optionally, the chemical formula of the precursor material is Ni x Fe y Mn z M 1-x-y-z (OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.
[0017] Optionally, the chemical formula of the primary material is Ni x Fe y Mn z M 1-x-y-zO2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0018] Optionally, the mixing ratio of the precursor material and the sodium source is a molar ratio of metal cations to sodium ions in the precursor material of 1:n, wherein 0.95≤n≤1.15.
[0019] Optionally, the sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium acetate.
[0020] Optionally, the transition metal M element source is nanoscale particles.
[0021] Optionally, the first calcination is a multi-stage calcination. The multi-stage calcination process includes raising the temperature to 400-550°C at a heating rate of 3-6°C / min for pre-sintering, and the pre-sintering time is 4-8h; then raising the temperature to 800-1100°C at a heating rate of 3-6°C / min for sintering, and the sintering time is 10-24h; cooling to room temperature after sintering.
[0022] Optionally, the second calcination temperature is 300-750° C. and the time is 5-10 h.
[0023] The present application also provides a sodium ion secondary battery, the raw materials of which include the positive electrode material of the sodium ion secondary battery.
[0024] The present application also provides an electrical device comprising the sodium ion secondary battery.
[0025] Compared with the prior art, the beneficial effects of this application include:
[0026] The present invention provides a battery, wherein the positive electrode active material in the positive electrode sheet of the battery is Na doped with a metal element having a valence of +2, +3, +4, +5 or +6. z Ni x Fe y Mn 1-x-y O2 sodium battery positive electrode material, by regulating the O3 structure of the sodium battery positive electrode material in the fully charged state - Ions relative to O 2- The molar amount is ≤2.5%, which increases the bonding strength between the doped metal element and oxygen and reduces the highly active O - The free oxygen content makes the sodium-ion battery O3 structure have strong structural stability, inhibiting the formation of O - The side reaction between free oxygen and the electrolyte can significantly improve the cycle stability of the material while ensuring the release of a higher gram capacity.
[0027] The preparation method provided in the present application is simple and convenient, does not require an additional water washing step, reduces energy consumption and can also obtain a positive electrode material with performance advantages.
[0028] The sodium ion battery provided by the present application has good energy density and cycle life, high gram capacity, and does not produce gas during use. The electrical equipment provided by the present application has excellent electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0030] Figure 1 This is a SEM spectrum of the positive electrode material of the sodium ion secondary battery prepared in Example 1;
[0031] Figure 2 Schematic diagram comparing the cycle capacity retention rates of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0032] As used herein:
[0033] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0034] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0035] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0036] In these examples, parts and percentages are by mass unless otherwise indicated.
[0037] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0038] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0039] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0040] In a first aspect, the present application provides a positive electrode material for a sodium ion secondary battery, wherein the chemical formula of the positive electrode material for the sodium ion battery is Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1, and the M element is a metal element with a valence ≥2.
[0041] Wherein, a can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, or any value greater than or equal to 0.9 and less than or equal to 1.05. x can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval between greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. y can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. z can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval between greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. 1-xyz can be any value or interval between greater than 0 and less than 1.
[0042] In an optional embodiment, the M element includes at least one of Al, Ti, Zr, Y, La, Ca, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0043] The present application also provides a method for preparing a positive electrode material for a sodium ion secondary battery, comprising:
[0044] Mixing the solutions of the nickel source, the iron source, the manganese source and the first M element source to obtain a mixed solution, and obtaining a precursor material by a coprecipitation method;
[0045] The precursor material is mixed with a sodium source and then first calcined, and then cooled to obtain a primary material;
[0046] The primary material is mixed with a second M element source and then subjected to a second calcination to obtain the positive electrode material of the sodium ion battery.
[0047] In an optional embodiment, the nickel source includes nickel sulfate; the iron source includes iron sulfate; and the manganese source includes manganese sulfate.
[0048] In an optional embodiment, the M element source includes at least one sulfate of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0049] In an optional embodiment, the metal element in the second M element source includes at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Zr, Co, Ta, Mo, and Nb.
[0050] In an optional embodiment, after the precursor material is prepared, it also includes solid-liquid separation, washing, and drying processes, and the drying temperature is 100-300° C. and the time is 2-6 hours.
[0051] Optionally, the drying temperature may be 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., 210° C., 220° C., 230° C., 240° C., 250° C., 260° C., 270° C., 280° C., 290° C., 300° C., or any value between 100-300° C. The drying time may be 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, or any value between 2-6 h.
[0052] Optionally, the chemical formula of the precursor material is Ni x Fe y Mn z M 1-x-y-z (OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.
[0053] Wherein, x can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval between greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. y can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. z can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval between greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. 1-xyz can be any value or interval between greater than 0 and less than 1.
[0054] Optionally, the chemical formula of the primary material is Ni x Fe y Mn z M 1-x-y-z O2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.0.
[0055] Optionally, x can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. y can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. z can be 0.02, 0.06, 0.08, 0.12, 0.16, 0.2, 0.24, 0.28, 0.32, 0.36, 0.4, 0.44, 0.48, 0.52, 0.56, 0.6, 0.64, 0.68, 0.72, 0.76, 0.8, 0.84, 0.86, 0.92, 0.98, 0.99, or any value or interval between greater than 0 and less than 1, such as 0.01-0.1, 0.01-0.2, 0.01-0.3, 0.01-0.4, 0.01-0.5, 0.01-0.6, 0.01-0.7, 0.01-0.8, 0.01-0.99, etc. 1-xyz can be any value or interval between greater than 0 and less than 1.
[0056] In an optional embodiment, the mixing ratio of the precursor material and the sodium source is a molar ratio of metal cations to sodium ions in the precursor material of 1:n, wherein 0.95≤n≤1.15.
[0057] Optionally, the molar ratio of metal cations to sodium ions in the precursor material can be 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, 1:1.1, 1:1.11, 1:1.12, 1:1.13, 1:1.14, 1:1.15, or any value in the range of 1:0.95-1.15.
[0058] In an optional embodiment, the sodium source includes one or more of sodium carbonate, sodium hydroxide, and sodium acetate.
[0059] In an optional embodiment, the transition metal M element source is nanoscale particles.
[0060] In an optional embodiment, the first calcination is a multi-stage calcination. The multi-stage calcination process includes raising the temperature to 400-550°C at a heating rate of 3-6°C / min for pre-sintering, and the pre-sintering time is 4-8h; then raising the temperature to 800-1100°C at a heating rate of 3-6°C / min for sintering, and the sintering time is 10-24h; cooling to room temperature after sintering.
[0061] Optionally, the heating rate during the pre-sintering can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, or any value between 3-6°C / min; the pre-sintering temperature can be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or any value between 400-550°C; the pre-sintering time can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value between 4-8h. The heating rate of the sintering can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, or any value between 3-6°C / min; the temperature during the sintering can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 960°C, 970°C, 980°C, 990°C, 100 The sintering temperature may be 0°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, or any value between 800-1100°C; the sintering time may be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, or any value between 10-24h.
[0062] In an optional embodiment, the second calcination is carried out at a temperature of 300-750° C. and for a time of 5-10 h.
[0063] The dimension of the second calcination can be 300° C., 320° C., 340° C., 360° C., 380° C., 400° C., 420° C., 440° C., 460° C., 480° C., 500° C., 520° C., 540° C., 560° C., 580° C., 600° C., 620° C., 640° C., 660° C., 680° C., 700° C., 720° C., 750° C., or any value between 300-750° C. The time of the second calcination can be 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, or any value between 5-10 h.
[0064] In a third aspect, the present application also provides a sodium ion secondary battery, the raw materials of which include the positive electrode material of the sodium ion secondary battery.
[0065] In an optional embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer formed on the surface of the positive electrode current collector. The positive electrode material layer includes the positive electrode material of the sodium ion secondary battery.
[0066] In an optional embodiment, the positive electrode current collector includes one of copper foil, aluminum foil, titanium foil, nickel foil, iron foil and zinc foil.
[0067] In an optional embodiment, the positive electrode material layer includes a positive electrode active material, a conductive agent and a binder. The positive electrode material layer is obtained by coating a positive electrode slurry including a positive electrode active material, a conductive agent, a binder and a solvent onto a positive electrode current collector, and then rolling, die-cutting and baking.
[0068] In an alternative embodiment, the solvent comprises N-methylpyrrolidone.
[0069] In an optional embodiment, the conductive agent includes one or more of electric carbon black (SP), carbon fiber (CF), acetylene black, Ketjen black, graphene and carbon nanotubes. The binder includes one or more of fluorine-containing resin, polypropylene resin, fiber-type binder and polyimide-type binder.
[0070] In an optional embodiment, based on 100wt% of the positive electrode active layer itself, the mass of the positive electrode active material may be 90-99wt%; the mass of the conductive agent is 0.5-5wt%; and the mass of the binder is 0.5-5wt%.
[0071] In an optional embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector.
[0072] In an optional embodiment, the negative electrode current collector includes copper foil; and the negative electrode material layer includes a negative electrode active material, a conductive agent, and a binder.
[0073] In an optional embodiment, the negative electrode material layer is obtained by coating a negative electrode slurry containing a negative electrode active material, a conductive agent, a binder and a solvent onto a negative electrode current collector, and then rolling, die-cutting and baking.
[0074] In an optional embodiment, the negative electrode active material includes one or more of artificial graphite, natural graphite, silicon-carbon negative electrode, hard carbon and sodium titanate. The conductive agent includes one or more of conductive carbon black, carbon fiber, acetylene black, Ketjen black, graphene and carbon nanotubes. The binder includes one or more of fluorine-containing resin, polypropylene resin, fiber-type binder, rubber-type binder and polyimide-type binder.
[0075] In an optional embodiment, based on 100wt% of the mass of the negative electrode material layer itself, the content of the negative electrode active material may be 90-99wt%; the mass of the conductive agent is 0.5-5wt%; and the mass of the binder is 0.5-5wt%.
[0076] In an alternative embodiment, the electrolyte includes a sodium salt, a solvent and an additive.
[0077] In an alternative embodiment, the solvent includes one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, ethylene glycol dimethyl ether and dioxolane.
[0078] In an optional embodiment, the additive includes one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), propene sultone (1,3-PS-PST), dithiodifluoroethane (DTD), and sodium difluorooxalatoborate (NaDFOB).
[0079] In a fourth aspect, the present application also provides an electrical device comprising the sodium ion secondary battery.
[0080] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0081] Example 1
[0082] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0083] Step 1: Mix nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and titanium sulfate solution in a ratio of Ni:Fe:Mn:Al:Ti=40:20:30:5:5, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.8, and then obtain the precursor material Ni by coprecipitation. 0.4 Fe 0.2 Mn 0.3 Ti 0.05 Al 0.05 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 150°C for 5h.
[0084] Step 2: Precursor material Ni 0.4 Fe 0.2 Mn 0.3 Ti 0.05 Al 0.05(OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h of pre-sintering in an air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h in an air atmosphere. After sintering, the positive electrode material Na was cooled with the furnace to obtain 1.01 Ni 0.4 Fe 0.2 Mn 0.3 Ti 0.05 Al 0.05 O2, crush the material through a roller mill / air flow crusher, and sieve it through 300 mesh for later use.
[0085] Step 3: Add Na to the positive electrode material 1.01 Ni 0.4 Fe 0.2 Mn 0.3 Ti 0.05 Al 0.05 Al2O3 with a particle size of 30-200nm was added to O2, and the added amount was 0.02%wt of the mass percentage of the positive electrode material. After mixing evenly, it was calcined at 650℃ for 6h to finally obtain the sodium positive electrode sample Na coated with Al on the surface. 101 Ni 04 Fe 02 Mn 03 Ti 005 Al 005 O2, and it is a single crystal material, D50 = 4.2μm, BET is 0.45m 2 / g, the SEM spectrum of the prepared positive electrode material of the sodium ion secondary battery is as follows Figure 1 shown.
[0086] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode active layer coated on an aluminum foil current collector to make a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to make a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus a ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0087] Example 2
[0088] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0089] Step 1: Mix nickel sulfate, manganese sulfate, iron sulfate and cobalt sulfate solutions in a ratio of Ni:Fe:Mn:Co=30:20:45:5, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.4, and then obtain the precursor material Ni by coprecipitation. 0.3 Fe 0.2 Mn 0.45 Co 0.05 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0090] Step 2: Precursor material Ni 0.3 Fe 0.2 Mn 0.45 Co 0.05 (OH)2 and sodium carbonate were weighed according to the molar ratio of metal cations to Na ions in the precursor of 1:1.05, and the two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was increased to 400°C at a heating rate of 3°C / min for 8h pre-sintering in an air atmosphere, and then the temperature was increased to 940°C at a heating rate of 3°C / min for 16h in an atmosphere containing 30% oxygen. After sintering, the positive electrode material Na was cooled with the furnace to obtain 0.98 Ni 0.3 Fe 0.2 Mn 0.45 Co 0.05 O2, crush the material through a roller mill / air flow crusher, and sieve it through 300 mesh for later use.
[0091] Step 3: Add Na to the positive electrode material 0.98 Ni 0.3 Fe 0.2 Mn 0.45 Co 0.05 Add ZrO with a particle size of 30-200nm to O2, the addition amount is 1500ppm; SrO with a particle size of 30-200nm, the addition amount is 650ppm; Al2O3 with a particle size of 30-200nm, the addition amount is 1000ppm. After mixing evenly, calcined at 580℃ for 6h, and finally the sodium positive electrode sample Na with surface co-doped Zr / Sr / Al was obtained. 0.98 Ni 0.3 Fe 0.2 Mn 0.45 Co 0.05 O2, and it is a single crystal material, D50 = 3.95μm, BET is 0.49m2 / g.
[0092] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to form a positive electrode active layer coated on an aluminum foil current collector to form a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to form a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0093] Example 3
[0094] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0095] Step 1: Mix nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and copper sulfate solutions in a ratio of Ni:Fe:Mn:Cu:Al=33:22:35:5:5, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.6, and then obtain the precursor material Ni by coprecipitation. 0.33 Fe 0.22 Mn 0.35 Cu 0.05 Al 0.05 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0096] The parameters of step 2 and step 3 are the same as those of Example 1, and Na 0.98 Ni 0.33 Fe 0.22 Mn 0.35 Cu 0.05 Al 0.05 O2 sample, and it is a single crystal material, D50 = 4.13μm, BET is 0.42m 2 / g.
[0097] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to form a positive electrode active layer coated on an aluminum foil current collector to form a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to form a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0098] Example 4
[0099] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0100] Step 1: Mix nickel sulfate, manganese sulfate, iron sulfate, aluminum sulfate and copper sulfate solutions in a molar ratio of Ni:Fe:Mn:Cu:Al=35:20:35:5:5, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.5, and then obtain the precursor material Ni by coprecipitation. 0.33 Fe 0.22 Mn 0.35 Cu 0.05 Al 0.05 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0101] The parameters in step 2 are the same as those in Example 1.
[0102] Step 3: Obtain material Na in step 2 1.02 Ni 0.4 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 O2, add 700ppm of WO3 with a particle size of 30-200nm and 2000ppm of CaO, mix well and calcine at 710℃ for 8h, and finally obtain sample Na 1.02 Ni 0.35 Fe 0.20 Mn 0.35 Cu 0.05 Al 0.05 O2, and it is a single crystal material, D50 = 2.85 μm, BET is 0.51 m 2 / g.
[0103] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to form a positive electrode active layer coated on an aluminum foil current collector to form a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to form a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0104] Example 5
[0105] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0106] The parameters of step 1 and step 2 are the same as those of embodiment 4.
[0107] Step 3: Obtain material Na in step 2 1.02 Ni 0.4 Fe 0.2 Mn 0.35 Cu 0.05 Al 0.05 In O2, the addition amounts of Al2O3 and TiO2 were 750ppm and 1250ppm respectively, and after being mixed evenly, they were calcined at 700℃ for 8h to finally obtain the sample Na 1.02 Ni 0.33 Fe 0.22 Mn 0.35 Cu 0.05 Al 0.05 O2, and it is a single crystal material, D50 = 3.72μm, BET is 0.487m 2 / g.
[0108] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to form a positive electrode active layer coated on an aluminum foil current collector to form a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to form a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0109] Example 6
[0110] This embodiment provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0111] Step 1: Mix nickel sulfate, manganese sulfate, iron sulfate, zinc sulfate and thallium sulfate solution in a ratio of Ni:Fe:Mn:Zn:Ta=30:20:30:10:5, then add 2 mol / L ammonia water and sodium hydroxide solution to adjust the pH value to 11.8, and then obtain the precursor material Ni by coprecipitation. 0.30 Fe 0.2 Mn 0.35 Zn 0.1 Ta 0.05 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0112] Step 2: Parameters are the same as in Example 1.
[0113] Step 3: Add Na to the positive electrode material 1.01 Ni 0.3 Fe 0.2 Mn 0.35 Zn 0.1 Ta 0.05 Al2O3 and Y2O3 with a particle size of 30-200 nm were added to O2 in an amount of 500 ppm and 1100 ppm respectively. After mixing evenly, the mixture was calcined at 680 ° C for 8 h to obtain the sample Na 1.01 Ni 0.3 Fe 0.2 Mn 0.35 Zn 0.1 Ta 0.05 O2, and it is a single crystal material, D50 = 4.28 μm, BET is 0.52 m 2 / g.
[0114] This embodiment also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to form a positive electrode active layer coated on an aluminum foil current collector to form a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to form a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are performed.
[0115] Comparative Example 1
[0116] This comparative example provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0117] Step 1: Mix nickel sulfate, manganese sulfate and iron sulfate in a ratio of Ni:Fe:Mn=33:33:34, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.9, and then obtain the precursor material Ni by coprecipitation. 0.33 Fe 0.33 Mn 0.34 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0118] Step 2: The parameters are the same as those in Example 1. Air flow crushing and sieving are performed to finally obtain the sample Na 1.01 Ni 0.33 Fe 0.33 Mn 0.34 O2, and it is a single crystal material, D50 = 4.58 μm, BET is 0.489 m2 / g.
[0119] This comparative example also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode active layer coated on an aluminum foil current collector to make a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to make a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are carried out.
[0120] Comparative Example 2
[0121] This comparative example provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0122] Step 1: Mix nickel sulfate, manganese sulfate and iron sulfate in a ratio of Ni:Fe:Mn=33:33:34, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.6, and then obtain the precursor material Ni by coprecipitation. 0.33 Fe 0.33 Mn 0.34 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0123] Step 2: Precursor material Ni 0.33 Fe 0.33 Mn 0.34 200ppm of SrO was added to (OH)2, and the above two substances were mixed evenly, and then sintered in stages in a sintering furnace: first, the temperature was raised to 400℃ at a heating rate of 3℃ / min for 8h pre-sintering in an air atmosphere, and then the temperature was raised to 940℃ at a heating rate of 3℃ / min for 16h in an air atmosphere. After sintering, the positive electrode material was cooled in the furnace and obtained. After air flow crushing, the sample Na 1.01 Ni 0.33 Fe 0.33 Mn 0.34 O2, and it is a single crystal material, D50 = 4.1 μm, BET is 0.5 m 2 / g.
[0124] This comparative example also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode active layer coated on an aluminum foil current collector to make a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to make a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are carried out.
[0125] Comparative Example 3
[0126] This comparative example provides a positive electrode material for a sodium ion secondary battery, and the preparation method is as follows:
[0127] Step 1: Mix nickel sulfate, manganese sulfate and iron sulfate in a ratio of Ni:Fe:Mn=30:50:20, then add 2 mol / L ammonia water and sodium hydroxide solution to the solution to adjust the pH value to 11.2, and then obtain the precursor material Ni by coprecipitation. 0.3 Fe 0.5 Mn 0.2 (OH)2, and then the obtained precipitate was filtered, washed, and dried at 200°C for 5h.
[0128] Step 2: The parameters are the same as those in Example 1. Air flow crushing and sieving are performed to finally obtain the sample Na 1.01 Ni 0.30 Fe 0.50 Mn 0.20 O2, and it is a single crystal material, D50 = 4.1 μm, BET is 0.5 m 2 / g.
[0129] This comparative example also provides a sodium ion battery: its raw materials include the above-mentioned positive electrode material PVDF binder, sulfur / polyacrylonitrile copolymer, and carbon nanotubes in a ratio of 95.5%:1.5%:2%:1% to make a positive electrode active layer coated on an aluminum foil current collector to make a positive electrode sheet. The negative electrode sheet uses hard carbon negative electrode material, styrene-butadiene rubber, sodium carboxymethyl cellulose binder, and carbon black in a ratio of 94.6%:1.5%:1.4%:2.5% to make a negative electrode active layer coated on an aluminum foil current collector. The electrolyte is propylene carbonate, ethylene carbonate, and dimethyl carbonate mixed in a mass ratio of 1:1:1, and then the sodium salt sodium hexafluorophosphate is dissolved in the mixed solvent to prepare a 1 mol / L electrolyte. A polyethylene film or a polyethylene plus ceramic coating film is selected as a diaphragm. The remaining steps are assembled into a sodium ion battery according to conventional methods, and the corresponding electrical performance tests are carried out.
[0130] The test of Examples 1-6 and Comparative Examples 1-3, the cycle capacity retention rate is compared Figure 2 The data results are shown in Table 1:
[0131] Table 1 Test data results
[0132]
[0133]
[0134] As can be seen from the above table, each embodiment is compared with comparative examples 1-3. a Ni x Fe y Mn z M 1-x-y-z By introducing metal elements with a valence of ≥+2 and optimizing the appropriate content in the O2 positive electrode material, the stability of the material's crystal structure is effectively enhanced. The provided sodium positive electrode material not only has a significant improvement in gram capacity compared to the positive electrode material in the comparative example, but also has a higher cycle capacity retention rate. The molar ratio of O- in the positive electrode material after cycling is relatively low, indicating that the O2- lattice oxygen in the positive electrode material does not participate in charge transfer during the charging and discharging process, thereby maintaining the integrity of the anion framework of the positive electrode material.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0136] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A positive electrode material for a sodium ion secondary battery, characterized in that: The chemical formula of the positive electrode material of sodium ion battery is Na a Ni x Fe y Mn z M 1-x-y-z O2, wherein 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1, and the M element is a metal element with a valence ≥2.
2. The positive electrode material for a sodium ion secondary battery according to claim 1, characterized in that: The M element includes at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Co, Ta, Mo, and Nb.
3. A method for preparing a positive electrode material for a sodium ion secondary battery according to claim 1 or 2, characterized in that: include: Mixing the solutions of the nickel source, the iron source, the manganese source and the first M element source to obtain a mixed solution, and obtaining a precursor material by a coprecipitation method; The precursor material is mixed with a sodium source and then first calcined, and then cooled to obtain a primary material; The primary material is mixed with a second M element source and then subjected to a second calcination to obtain the positive electrode material of the sodium ion battery.
4. The method for preparing a positive electrode material for a sodium ion secondary battery according to claim 3, characterized in that: At least one of the following conditions is met: a. The nickel source comprises nickel sulfate; b. The iron source comprises ferric sulfate; c. The manganese source comprises manganese sulfate; d. The first M element source includes a sulfate of at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Co, Ta, Mo, and Nb; e. The metal element in the second M element source includes at least one of Al, Ti, Zr, Y, Zn, Cu, W, Sr, Al, Co, Ta, Mo, and Nb; f. After the precursor material is prepared, the process further includes solid-liquid separation, washing and drying, wherein the drying temperature is 100-300°C and the drying time is 2-6h; g. The chemical formula of the precursor material is Ni x Fe y Mn z M 1-x-y-z (OH)2, wherein 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.
5. The method for preparing the positive electrode material of the sodium ion secondary battery according to claim 3, characterized in that: The chemical formula of the primary material is Ni x Fe y Mn z M 1-x-y-z O2, where 0.9≤a≤1.05, 0<x<1.0, 0<y<1.0, 0<z<1.0, 0<1-xyz<1.
0.
6. The method for preparing the positive electrode material of the sodium ion secondary battery according to claim 5, characterized in that: At least one of the following conditions is met: h. The mixing ratio of the precursor material and the sodium source is a molar ratio of the metal cations to the sodium ions in the precursor material of 1:n, wherein 0.95≤n≤1.15; i. The sodium source comprises one or more of sodium carbonate, sodium hydroxide and sodium acetate; j. The second M element source is nano-scale particles.
7. The method for preparing a positive electrode material for a sodium ion secondary battery according to claim 6, characterized in that: At least one of the following conditions is met: k. The first calcination is a multi-stage calcination; 1. The temperature of the second calcination is 300-750°C and the time is 5-10h.
8. The method for preparing the positive electrode material of the sodium ion secondary battery according to claim 7, characterized in that: The multi-stage calcination process includes raising the temperature to 400-550°C at a heating rate of 3-6°C / min for pre-sintering, and the pre-sintering time is 4-8h; and then raising the temperature to 800-1100°C at a heating rate of 3-6°C / min for sintering, and the sintering time is 10-24h; After sintering, cool to room temperature.
9. A sodium ion secondary battery, characterized in that: The raw material includes the positive electrode material of the sodium ion secondary battery according to claim 1 or 2.
10. An electrical equipment, characterized in that: Includes the sodium ion secondary battery according to claim 9.